QUADRATIC DYNAMICAL SYSTEMS IN BIOLOGY - Urokova, Mehriniso (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
In this paper we consider a continuous time dynamical systemÂ Â arising from population biology. We find explicit formula for trajectories of this system and calculate its limit point when time goes to infinite.